2016
DOI: 10.1108/ijrdm-09-2015-0140
|View full text |Cite
|
Sign up to set email alerts
|

The digitalization of retailing: an exploratory framework

Abstract: Purpose – Digitalization denotes an on-going transformation of great importance for the retail sector. The purpose of this paper is to analyse the phenomenon of the digitalization of retailing by developing a conceptual framework that can be used to further delineate current transformations of the retailer-consumer interface. Design/methodology/approach – This paper develops a framework for digitalization in the retail-consumer interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
354
0
38

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(400 citation statements)
references
References 92 publications
8
354
0
38
Order By: Relevance
“…24 The implications of this paper are several. First, it extends the growing body of research on innovation in retailing (Demirkan and Spohrer, 2014;Pantano, 2014;Hagberg et al, 2016;, and smart retailing (Kim et al, 2017;Pantano and Timmermans, 2014;Priporas et al, 2017;Roy et al, 2017;Vrontis et al, 2017), by offering a clear framework that describes the extent to which retailing can be improved through the systematically use of smart technologies, employed to support several aspects of the process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 The implications of this paper are several. First, it extends the growing body of research on innovation in retailing (Demirkan and Spohrer, 2014;Pantano, 2014;Hagberg et al, 2016;, and smart retailing (Kim et al, 2017;Pantano and Timmermans, 2014;Priporas et al, 2017;Roy et al, 2017;Vrontis et al, 2017), by offering a clear framework that describes the extent to which retailing can be improved through the systematically use of smart technologies, employed to support several aspects of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing, these tools allow consumers to easily and directly search and compare products, (virtually) taste items, access customised information, receive shopping assistance, and pay with benefits (Demirkan and Spohrer, 2014;Hagberg et al, 2016;Korouthanassis et al, 2007;Pantano and Priporas 2016;Pantano and Viassone, 2015;Papagiannidis et al, 2014). In fact, the introduction of these new technologies at physical points of sale may solve several emerging problems in traditional retailing such as a crowded retail environment, limited opening hours, temporary non-availability of a sales assistant, and the slow speed of reply and monetary transactions (payments).…”
Section: Drivers Of Innovation In Retailingmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, concerning the organizational process, smart technologies affect the methods of collecting data from consumers, managing information, transferring knowledge from firms to consumers and vice versa (Leitner and Grechenig, 2009; partnership with clients, who become active actors working in cooperation with retailers towards the common goal of producing a more satisfying service, while pushing retailers to develop new capabilities for actively responding to changeable markets and successfully managing innovation (Hagberg et al, 2015;Kindstrom et al, 2013). Concerning selling activities, smart technologies are able to change the way in which consumers access and consume services and products, as well as the building and maintenance of relationships with sellers.…”
Section: Smart Retailingmentioning
confidence: 99%
“…In fact, as Hagberg, Egels‐Zandén, and Sundström () argues, mobile phones, and in particular smartphones, are changing the way that consumers shop and relate to the retail landscape. Although earlier studies have often shown that mobile phones were only marginally involved in shopping, new surveys and studies suggest that they are now being integrated into everyday shopping practices and the use of smartphones is also increasing globally.…”
Section: Uss Impacted By Dssmentioning
confidence: 99%